The Association Between Frontotemporal Lobar Degeneration and Bullous Pemphigoid. - Katisko, Kasper; Kokkonen, Nina; Krüger, Johanna; Hartikainen, Päivi; Koivisto, Anne M; Helisalmi, Seppo; Korhonen, Ville E; Kokki, Merja; Tuusa, Jussi; Herukka, Sanna-Kaisa; Solje, Eino; Haapasalo, Annakaisa; et al. (J Alzheimers Dis, 2018)
Recent studies have shown an epidemiological and immunological association between bullous pemphigoid (BP) and several neurological or psychiatric diseases. Here, our aim was for the first time to specify whether an association exists between BP and frontotemporal lobar degeneration (FTLD). Medical histories of FTLD patients (N = 196) were screened for clinical comorbidity, and BP180 and BP230 autoantibodies were analyzed in the sera of FTLD patients (N = 70, including 24 C9orf72 repeat expansion carriers) by BP180-NC16A-ELISA and BP230-ELISA. One FTLD patient (C9orf72 repeat expansion carrier) had a comorbid diagnosis of BP. Increased levels of serum BP180 autoantibodies (cutoff value >9 U/ml) were detected more often in FTLD patients (10.0%) than in controls (4.9%). Moreover, elevated levels of both BP180 and BP230 autoantibodies were found more often in C9orf72 repeat expansion-carrying FTLD than non-carrying patients or controls. However, none of these differences reached a statistical significance likely due to our limited cohort size. In conclusion, our findings suggest that subset of FTLD patients especially with the C9orf72 repeat expansion may have an immunological association with BP.